Gym entry fees act as a barrier to exercising in community gyms for young adults with disability: A mixed methods study - Rachel A. Kennedy; Georgia McKenzie; Nora Shields (JSAMS Plus)
Background: Cost is a barrier to exercise for young adults with disability aged 18–35 years. Few studies have investigated this barrier in depth. We explored the cost barrier to exercise for young adults with disability in the context of community gyms. Method: A mixed methods study was completed. Data were collected in three consecutive phases. Phase 1 was a survey of entry options reflecting current practice in 59 community gyms. Phase 2 comprised semi-structured interviews with 20 young adults with disability and 25 community gym staff. Phase 3 involved three focus groups with key informants (n ​= ​20 total) from disability, recreation, and policy sectors. Quantitative data were analysed descriptively. Qualitative data were analysed using inductive thematic analysis. Results: Gyms estimated 10 ​% of members had a disability. The overarching theme was a mismatch between the wants and needs of young adults with disability with what community gyms and disability systems offer. Three subthemes illustrated this: young adults need flexibility but current practices limit gym entry options; young adults seek value for money, but current practices advocate value-add; and young adults desire community participation, but current practices inadvertently reinforce a rehabilitation model. A further subtheme —financial viability—related to how recreation centres were often not financially sustainable limiting gym entry practices. Conclusion: Despite broadly supportive recreation and policy sectors, current practices and funding systems are misaligned with the wants and needs of young adults with disability, and often incongruent with societal values of social inclusion and community-based physical activity.